The Berenstain Bears forget their manners - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1985)
Mama Bear comes up with a plan to correct the Bear family's rude behavior.
School Library Journal.
3.0
K-3
Keywords: Bears -- Fiction; Behavior -- Fiction; Berenstain Bears (Fictitious characters) -- Fiction; Courtesy -- Fiction; Bears -- Fiction; Berenstain Bears (Fictitious characters) -- Fiction; Courtesy -- Fiction; Human behavior -- Fiction